Diversity patterns of planktonic microeukaryote communities in tropical floodplain lakes based on 18S rDNA gene sequences. (7th June 2019) - Machado, Karine Borges; Targueta, Cíntia Pelegrineti; Antunes, Adriana Maria; Soares, Thannya Nascimento; Telles, Mariana Pires de Campos; Logares, Ramiro; Vieira, Ludgero Cardoso Galli; Huszar, Vera Lúcia de Moraes; Nabout, JoÃo Carlos
Abstract: The aquatic microbiota plays key roles in ecosystem processes; however, the mechanisms that influence their biogeographic patterns are not yet fully understood. Using high-throughput 18S rDNA gene sequencing, we investigated the composition of planktonic microeukaryotes (organisms sampled using a 68-μm plankton net) in 27 floodplain lakes of the Araguaia River, central Brazil and explored the influence of environmental and spatial factors for communities considering taxonomic and trophic groups. Of the 807 operational taxonomic units (OTUs) observed, Chlorophyta and Charophyta were the groups with greater abundance. Beta diversity was high, and the similarity of communities decreased as the geographic distance increased. We found a shared explanation between environmental and spatial predictors for total and autotrophic microbiota. Environmental variables influence only mixotrophic microbiota. These results suggest an OTU turnover along the floodplain and a spatially structured composition. This spatial pattern can be derived from the association with extrinsic factors, such as spatially structured environmental variables, that generate spatial dependence. However, the relationship between the composition of microbiota and environmental conditions is still unclear.